2018
DOI: 10.1039/c8sm01388h
|View full text |Cite|
|
Sign up to set email alerts
|

Physical crosslinking of hyaluronic acid in the presence of phospholipids in an aqueous nano-environment

Abstract: The presence of phospholipids and longer hyaluronic acid chains promote long-lasting networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…We have shown that, depending on the degree of crosslinking and on the interaction with other components of the extracellular matrix, the diffusion of tracer particles in hyaluronan networks can change drastically. This is interesting when considering physiological situations where physical 80 or chemical 71 crosslinking occurs, as crosslinking is likely to influence the diffusion of nutrients, growth factors and other signaling macromolecules through tissues. While semidilute solutions and transiently crosslinked networks of hyaluronan hinder particle transport through enhanced viscous drag, permanently crosslinked networks mainly exert a size exclusion effect whereby particle mobility is dependent on its size.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, depending on the degree of crosslinking and on the interaction with other components of the extracellular matrix, the diffusion of tracer particles in hyaluronan networks can change drastically. This is interesting when considering physiological situations where physical 80 or chemical 71 crosslinking occurs, as crosslinking is likely to influence the diffusion of nutrients, growth factors and other signaling macromolecules through tissues. While semidilute solutions and transiently crosslinked networks of hyaluronan hinder particle transport through enhanced viscous drag, permanently crosslinked networks mainly exert a size exclusion effect whereby particle mobility is dependent on its size.…”
Section: Discussionmentioning
confidence: 99%
“…The HA-PL interactions in SF has been shown to be an important factor in lubrication of AC system [2,[25][26][27][28]. Shorter chains, create more H-bonds with nearest neighbours atoms and this contributes to higher sti®ness in these chains, and in-°u ence its persistence length from its normal value [29,30]. On the other hand, longer chains are more prone to crosslinking [30].…”
Section: Discussionmentioning
confidence: 99%
“…Shorter chains, create more H-bonds with nearest neighbours atoms and this contributes to higher sti®ness in these chains, and in-°u ence its persistence length from its normal value [29,30]. On the other hand, longer chains are more prone to crosslinking [30]. The comparatively short-lived networks formed by short-chain HA may be of less signi¯cance than the more stable networks formed by long-chain HA with respect to viscoelastic and shock absorption properties.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to analyze the dynamics of each component, as well as the synergy between them. In [9][10][11], we focused on the tribological role of HA-PL interactions, an effect also investigated in [12] for its role in tribological surgical adjuvant. To continue building an understanding of synovial lubrication, we now study the inter-and intra-molecular properties of lubricin within synovial fluid.…”
Section: Introductionmentioning
confidence: 99%